Den Verlauf kontrollieren: Eine Ethnographie der waterscape von Gilgit, Pakistan. Ressourcen – Gemeinschaften – Überwachung - Grieser, Anna (transcript, 2018)
Ethnography of an urban waterscape in the desert in the highlands of Pakistan: While local players try to influence the course of water, economic resources and institutional commitment, governmental players endeavor to control behavior.